PERUBAHAN BUDAYA LOKAL DAN ISLAM BANJAR DALAM AKTIVITAS PENDULANGAN BATU PERMATA KHAS KALIMANTAN SELATAN - Rabiatul Adawiah; Inawati Mohammad Jainie; Halimatus Sakdiah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
South Kalimantan is not only rich in natural resources, but also rich in culture and religious values. This study aims to describe the local cultural traditions and Islam associated with the activity of "diamond" gemstone panning, which is one of the natural resources of South Kalimantan, as well as to examine the cultural changes in the diamond panning tradition. The research method used is a qualitative ethnographic method. Data analysis from observations, interviews and documents from diamond panners was conducted using Miles and Huberman's interactive model. The results showed that the local and Islamic cultures of the Banjar people were found before panning, during panning and after panning diamonds. Local culture such as visiting thieves, maintaining abstinence and speech (pamandiran) and Islamic culture such as visiting the pious, reading prayers, reading shalawat, faith, patience and tawakkal. Some of these traditions have changed, especially in the local culture, including the tools used for panning. Social change in panning activities is an evolutionary change where the shift in cultural traditions occurs slowly to adapt to internal and external factors so that the balance of the social system is maintained where malim, pious people, bosses/capital owners, panners perform their duties according to to their functions for the sustainability of panning activities. Keywords:Local culture, Islamic culture, diamond panning, social change